Normal withdrawal time correlates with polyp detection rate and adenoma detection rate: A quantitative observational study from a metropolitan Australian hospital. (2020) - Lin, Lei; Khaing, Myat Myat; Kellar, Petrina; Hartnell, Felicity; Croese, John; Hodgson, Ruth; James, Thomas; Franz, Robert; Hughes, Andrew; Shaw, Ian; Iswariah, Harish; Vandeleur, Ann; et al.
No abstract available